1993
DOI: 10.1016/0028-2243(93)90180-k
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pefloxacin/metronidazole and doxycycline/metronidazole in the treatment of laparoscopically confirmed acute pelvic inflammatory disease

Abstract: SummaryA double-blind, randomised study was conducted to compare the efficacy and safety of a combination of pefloxacin and metronidazole versus doxycycline and metronidazole in patients with pelvic inflamma tory disease (PID). The clinical diagnosis had to be confirmed by laparoscopy before patients were includ ed. Of the 74 patients who fulfilled the clinical criteria for PID, laparoscopy confirmed the diagnosis in only 40 patients (54%). The microorganism most frequently found as causative pathogen was Chla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…In a randomized clinical trial of 40 patients with laparoscopically confirmed salpingitis, combined doxycycline-metronidazole treatment exhibited a low clinical cure rate of 35%, with a 50% clinical improvement rate [21]. The low efficacy of this regimen was replicated in an observational study in the United Kingdom involving 135 women with PID, in which only 55% experienced a clinical cure 2 or 4 weeks after treatment [26].…”
Section: Doxycycline and Metronidazole Trialsmentioning
confidence: 96%
“…In a randomized clinical trial of 40 patients with laparoscopically confirmed salpingitis, combined doxycycline-metronidazole treatment exhibited a low clinical cure rate of 35%, with a 50% clinical improvement rate [21]. The low efficacy of this regimen was replicated in an observational study in the United Kingdom involving 135 women with PID, in which only 55% experienced a clinical cure 2 or 4 weeks after treatment [26].…”
Section: Doxycycline and Metronidazole Trialsmentioning
confidence: 96%
“…In a randomized clinical trial of 40 patients with laparoscopically confirmed salpingitis, combined doxycycline/metronidazole treatment exhibited a low clinical cure rate of 35%, with a 50% clinical improvement rate [50]. The low efficacy of this regimen was replicated…”
Section: Doxycycline and Metronidazole Trialsmentioning
confidence: 85%
“…Since the lack of anaerobic coverage with ofloxacin is a concern, emphasized by the high rate of treatment failure among patients with nongonococcal, nonchlamydial PID [40], the CDC suggests the optional addition of [50] Pefloxacin (800 mg/day) plus metronidazole (500 mg every 13% rate of adverse events [52] Comparator: clindamycin (900 mg iv.) plus gentamycin metronidazole [21].…”
Section: Fluoroquinolone Trialsmentioning
confidence: 99%
“…C'est notamment le cas des bêtalactamines, des cyclines et des fluoroquinolones ; la durée habituelle du traitement est de 14 jours, selon l'évolution [68] ; un suivi, clinique et bactériologique, est conseillé un à trois mois après la fin du traitement pour s'assurer de la réalité de la guérison. À l'heure actuelle, l'évolution des résistances bactériennes et la mise en évidence de nouveaux effets indésirables dus à des fluoroquinolones rendent le choix des antibiotiques délicat : la plupart des protocoles internationaux récents comme ceux des CDC d'Atlanta, du Royal College britannique et les recommandations européennes (European Guidelines) [69], fait appel à une fluoroquinolone associée au métronidazole [70]. Les fluoroquinolones possèdent en effet une bonne activité vis-à-vis de nombreux pathogènes ; leur pharmacocinétique et leur excellente diffusion tissulaire autorisent leur utilisation indifféremment par voie orale ou parentérale [71].…”
Section: Traitement Des Ighunclassified